LANGUAGE LEARNING DESIGN FOR PRONUNCIATION INSTRUCTION: LISTEN-AND-READ METHOD - Sariani, Sariani; Yaningsih, Yaningsih; Haslina, Welsi; El Khairat, Mutia (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
Regardless fewer studies have been conducted in pronunciation teaching, pronunciation has a significant role in language learning to make the meaningful communication occured, as pronouncing word in different ways will cause different in meaning of the word. Therefore, this article concentrated on the innovative language learning design particularly in pronunciation instruction in an EFL setting, in order to improve the students? phonemes of English, and their listening skill as well. This was a classroom research based on observation carried out in a class consisted of 26 students with basic proficiency level. The observation was conducted once a week in a 2x50 minutes teaching time, for 16 meetings. The last 25 minutes learning time was set for pronunciation. The procedure consisted of three activities: brainstorming words, applying the ?listen-and-read? method, and carrying out evaluation. The findings indicated that there was a significant improvement on students? ability in recognizing the sound of the language, and at the same time improving their pronunciation on being intelligible and comprehensible